SOCIAL FINANCE TAXONOMY IN TRANSITION TOWARDS A MORE SUSTAINABLE ECONOMY - Vasylchuk, Iryna; Slyusarenko, Kateryna; Kotane, Inta (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The successful development of a sustainable economy and society in together with the Sustainable Development Goals (SDG-2030) requires comprehensive and coordinated efforts of governments, businesses and civil society in order to establish unified and clear rules and regulations for economic activity. In order to reach this goal the European Union begun the development of EU sustainability taxonomy, which is to ensure an equal understanding of the content of activities of enterprises, projects and investments that meet sustainability criteria. So as to realize the potential of the market for social investments and loans, unification of approaches for understanding the main concepts of the social financing process is necessary. The purpose of the study is to develop proposals for the classification of subjects and objects of the subsystem of social finance consistent with sustainability taxonomy. The research applies methods of induction and deduction, scientific abstraction of theoretical generalization and comparative analysis while studying definitions, best practices of social investment and for developing the classification of social impact investments and social enterprises. The article provides coherent analysis of the formation of social entrepreneurship and finance in Ukraine. Based on the results of the study, the most relevant classification features of social enterprises and investments were developed and recommendations were made for integrating social finance taxonomy into sustainability taxonomy. The results of the research are of both theoretical and practical value.